1997
DOI: 10.1021/ja970320r
|View full text |Cite
|
Sign up to set email alerts
|

Angular and Distance Dependence of the Magnetic Properties of Oxo-Bridged Iron(III) Dimers

Abstract: The magnetic properties of oxo-bridged oxo-(carboxylato)-bridged and oxo-bis(carboxylato)-bridged iron(III) dimers are found to depend on the iron−(μ-O) distance as well as on the iron−(μ-O)−iron angle. With an angular and radial overlap model we account for both these dependencies. The use of an angular overlap model allows us to separate the σ donor properties of oxide as a ligand into the sσ and pσ contributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
149
2
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(184 citation statements)
references
References 45 publications
30
149
2
1
Order By: Relevance
“…Weihe and Güdel [19] recently analyzed the dependence of J on the Fe-O-Fe angle f and the average FeÀO distance r by using the angular and radial overlap model. They found that calculated J values increased with decreasing values of r and f. Our values of r 1.784(1) and f 169.6(6)8 fit precisely on the J À 100 cm À1 curve in Figure 3 of reference [19], in very good agreement with the observed J value. The model is therefore able to predict J values for new Fe-O-Fe complexes such as 1.…”
Section: Methodsmentioning
confidence: 99%
“…Weihe and Güdel [19] recently analyzed the dependence of J on the Fe-O-Fe angle f and the average FeÀO distance r by using the angular and radial overlap model. They found that calculated J values increased with decreasing values of r and f. Our values of r 1.784(1) and f 169.6(6)8 fit precisely on the J À 100 cm À1 curve in Figure 3 of reference [19], in very good agreement with the observed J value. The model is therefore able to predict J values for new Fe-O-Fe complexes such as 1.…”
Section: Methodsmentioning
confidence: 99%
“…[b] Calculated coupling constant according to the expression given by Gorun and Lippard [39] and in parenthesis that of Weihe and Güdel. [40] [c] Paramagnetic impurity with S 5 2, given in molar percentage. (1.44 ± 1.39 mm s À1 for 5).…”
mentioning
confidence: 99%
“…On the other hand, Weihe and Güdel [40] have recently derived a similar equation [Eq. (17)] which correlates J with R and F.…”
mentioning
confidence: 99%
“…7). It is interesting to compare the exchange interactions for complexes 2 (mediated by oxime -N-O-and O 2-) and 6 (mediated by oxime -N-O-and -OR), with the former almost five times stronger than the latter [58]. We can also compare the data for 6 to that previously reported for the complex [Fe 4 F 4 (Ph-sao) 4 (py) 4 ].…”
Section: Magnetic Propertiesmentioning
confidence: 78%